EDUKASI KESEHATAN TENTANG INFEKSI SOIL TRANSMITTED-HELMINTHS DENGAN MEDIA BOARD GAME DI SD IT AL MARHAMAH KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Selfi Renita Rusjdi; Refa Rahmaddiansyah; Muhammad Nur Alif Johar; Mutia Utami; gabriel septian hendra; Maisarah Fadhilah; Wulandari Wulandari; Ahmad Raffi Yustian; Siti Aisyah; Nilam Faizah Kaltsum; Selin Faysa Satiya (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Worm infections caused by soil-transmitted helminths (STH) occur almost throughout the world, especially in countries with tropical climates. In terms of prevalence, Indonesia ranks third in cases of worm infections, the majority of which infect school-aged children in coastal areas. This activity was carried out for students at SD IT Al Marhamah Kampung Dalam in Padang Pariaman Regency by providing education about preventing soil-transmitted helminth (STH) infections using board game media. The activity aims to increase students' knowledge regarding soil transmitted helminth infections and their prevention. This activity uses a descriptive observational approach, with the target covering students in grades 3 to 6 at SD IT Al Marhamah. The activity was carried out on February 11, 2023, at SD IT Al Marhamah Padang Pariaman with board game media to educate school children about worm infections. Activities consist of licensing, implementation of service, and evaluation. In total, 94 SD IT Al Marhamah Padang Pariaman students participated in service activities. In terms of distribution, there were 39 men and 55 women. Before the extension activities, a pretest was carried out. Then, education was carried out and continued with a post-test to assess students' knowledge of STH infections. The research results showed that there was an increase in the level of knowledge before and after the intervention. It was concluded that the final results of the activity showed that the increase in the level of knowledge of SD IT Al Marhamah students regarding soil transmitted helminth infections after being given counseling using the board game method showed that the intervention was successful. The students who took part in the activity were satisfied with the extension activity and gave a positive response.